Understanding Pediatric Norovirus Epidemiology: A Decade of Study among Ghanaian Children - Belinda L. Lartey; Osbourne Quaye; Susan A. Damanka; Chantal A. Agbemabiese; Joseph Armachie; Francis E. Dennis; Christabel Enweronu-Laryea; George E. Armah (Viruses, 2020)
Understanding the epidemiology of human norovirus infection in children within Ghana and the entire sub-Saharan African region, where future norovirus vaccines would have the greatest impact, is essential. We analyzed 1337 diarrheic stool samples collected from children <5 years from January 2008 to December 2017 and found 485 (36.2%) shedding the virus. GII.4 (54.1%), GII.3 (7.7%), GII.6 (5.3%), GII.17 (4.7%), and GII.5 (4.7%) were the most common norovirus genotypes. Although norovirus GII.4 remained the predominant capsid genotype throughout the study period, an increase in GII.6 and GII.3 capsid genotypes was observed in 2013 and 2014, respectively. The severity of clinical illness in children infected with GII.4 norovirus strains was similar to illness caused by non-GII.4 strains. Since the epidemiology of norovirus changes rapidly, establishment of systematic surveillance within sentinel sites across the country would enhance the monitoring of circulating norovirus strains and allow continuous understanding of norovirus infection in Ghana.